Common language effect size for correlations. Issue 3 (3rd July 2019) - Liu, Xiaofeng Steven; Carlson, Ryan; Kelley, Ken
Abstract: The Pearson correlation coefficient can be translated to a common language effect size, which shows the probability of obtaining a certain value on one variable, given the value on the other variable. This common language effect size makes the size of a correlation coefficient understandable to laypeople. Three examples are provided to demonstrate the application of the common language effect size in interpreting Pearson correlation coefficients and multiple correlation coefficients.